Analisis Z-Score Pada PT. Air Asia Indonesia Tbk. - Grace Sriati Mengga; Esti Membunga (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study discusses the health conditions of the aviation industry company, namely PT. Air Asia Indonesia Tbk. The purpose of this study was to determine the company's health condition in accordance with the results of the Z-Score of the Altman method at PT. Air Asia Indonesia Tbk. The data analysis method used is descriptive quantitative by calculating the numbers in the financial statements of PT. Air Asia Indonesia Tbk.. The data analysis technique used is the Altman Z-Score model. Data collection techniques are carried out through documentation of the data published by PT. Air Asia Indonesia Tbk. To determine the results in this study used the I. Altman Z-score model in 1968. The results of this study found that PT. Air Asia Indonesia Tbk for 4 (four) years experienced financial difficulties or was in the classification of high potential for bankruptcy. This has a direct impact on stock prices and earnings before interest and taxes which continue to decline.